1968
DOI: 10.1149/1.2411442
|View full text |Cite
|
Sign up to set email alerts
|

Ion Mobility in Crystals of a Mixed-Alkali Ferrite: K[sub x]Na[sub 1−x]Fe[sub 7]O[sub 11]

Abstract: A mixed alkali hexagonal ferrite phase K0.87Na0.13Fe7O11 , is reported. The unit cell and crystal density show it to be closely related to the known phase, KFe11O17 . In the temperature range 200°–500°C the Na+ ions are immobile, but the K+ ions exchange rapidly and completely with Na+ from molten salt. The self‐diffusion coefficients for K+ in K0.87Na0.13Fe7O11 , and Na+ in NaFe7O11 , have been determined as a function of temperature. Exchange from aqueous solution was found to be inhibited. The mobility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1968
1968
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…Early studies of intercalation focused on highly covalent oxides or sulfides (W, Mo, V, Nb, and Ti), whose corner or edge sharing creates channels for facile mass transport and ion conduction. Treating it as a variant of a symmetrical concentration cell using two identical hosts as described by Hever in 1968, Armand established an early mathematical model based on intercalation cells with two different hosts, although at the time it remained unclear which materials serve as ideal hosts. The first actual unsymmetrical intercalation cell that shuttled Li + back and forth was demonstrated by Lazzari and Scrosati .…”
Section: Intercalation Bypassmentioning
confidence: 99%
“…Early studies of intercalation focused on highly covalent oxides or sulfides (W, Mo, V, Nb, and Ti), whose corner or edge sharing creates channels for facile mass transport and ion conduction. Treating it as a variant of a symmetrical concentration cell using two identical hosts as described by Hever in 1968, Armand established an early mathematical model based on intercalation cells with two different hosts, although at the time it remained unclear which materials serve as ideal hosts. The first actual unsymmetrical intercalation cell that shuttled Li + back and forth was demonstrated by Lazzari and Scrosati .…”
Section: Intercalation Bypassmentioning
confidence: 99%
“…In the temperature range 1100~176 both Volpe and Reddy (7) and Crow (8) have found that nickel diffusivities decrease with decreasing oxygen pressure in the region 1 atm > Po2 > 10 -7 atm, with the pressure dependence varying with temperature and Poe. The results were interpreted in terms of nickel diffusion via both singly and doubly charged nickel vacancies.…”
Section: Diffusion Of Lcr In Nio Single Crystalsmentioning
confidence: 99%
“…being the single-cell reaction (z : 2) 0.5 O2 + 2 Li ~ Li20 (soln) [7] By taking into account the equilibrium constant of reaction [1], one obtains, for the emf of cell [4] 0,5 LifO…”
Section: Rt X~mentioning
confidence: 99%
“…Oxide thickness for short oxidation time and/or low oxidation temperature is proportional to the time and to the square root of the oxidation time for long time and/or high temperature. The rate constant in the former case (linear rate constant) is limited by the surface reaction rate for oxidation and the rate constant in the latter case (parabolic rate constant) is limited by the diffusion rate of oxidant in the oxide film (1). It was reported that these rate constants depend on the impurity concentration in silicon as well as the temperature and oxidizing ambient.…”
Section: Thermal Oxidation Of Arsenic-diffused Silicon Shinji Ohkawa ...mentioning
confidence: 99%